A New Train Technology Leads to a Revol ution in Transport Networks - Jurgen Gausemeier; Markus Henke; Xiaobo Liu; Bernd Riepe (Promet - Traffic&Transportation, 1970)
Securing of our future necessitates product and service innovations.These innovations will decisively contribute to thecreation of jobs and to the maintenance of high standard of livingas well as enabling sustainable development. Great opportunitiesfor products and services for the markets of tomorrowarise as a result of the combined growth of companies andeconomies, together with the dynamic development of technology.One rapidly growing innovation area is that of track-basedtransport systems. After an era of partial improvements to thefundamental techniques of the previous centwy, the time is ripeto move to new methods for the race to the future.